DISCOVERY LEARNING MODEL TO IMPROVE CREATIVE THINKING SKILLS AND ABILITY TO UNDERSTAND CONCEPTS IN OHM'S LAW MATERIAL: META ANALYSIS - Taurusi, Tutris; Septi, Sabila Eka; Osma, Ummi Shuhada (EduFisika: Jurnal Pendidikan Fisika, 2024)
This research is based on several articles published in articles found on Google Scholar throughout Indonesia from 2016 to 2023. Variables were analyzed using the descriptive method of systematic literature review by collecting data from written sources such as books, journals and sources related to improvement. discovery learning model to improve creative thinking skills and the ability to understand concepts in Ohm's law materials. The aim of this literature study research is to find out and see whether there is an increase in creative thinking skills and the ability to understand concepts through the application of the discovery learning learning model. The results of research literature show that the discovery learning model can improve creative thinking skills and the ability to understand concepts in Ohm's law material and improve material in several other subjects.